Divide throughout by "(x+1)" :
"\\frac{dy}{dx} + \\frac{(x+2)}{(x+1)} y= \\frac{2xe^{-x }}{(x + 1)}"
"IF = e^{\\int \\frac{(x+2)}{(x+1)}dx}"
"IF = e^{\\int 1+ \\frac{1}{(x+1)}dx}"
"IF = e^{x+ln|x+1|}"
"IF = (x + 1)e^{x}"
Multiply throughout by the Integrating factor :
"(x + 1)e^{x} * [\\frac{dy}{dx} + \\frac{(x+2)}{(x+1)} y = \\frac{2xe^{-x} }{ (x + 1)}]"
"\\frac{d}{dx}(y (x + 1)e^{x}) = (x + 1)e^{x} \\frac{2xe^{-x}}{(x + 1)}"
"\\frac{d}{dx}(y (x + 1)e^{x}) =2x"
Integrating :
"y(x + 1)e^{x} = x^2 + C"
"y = \\frac{x^2 + C}{(x+1)e^x}"
Clearly, since we have the "x + 1" in denominator, x cannot be equal to -1
This splits number line into intervals "(- \\infin , -1)" and "(-1 , \\infin)"
out of which "(-1 , \\infin)" is LARGER
So, "(-1 , \\infin)" "\\implies" ANSWER
Both terms, "\\frac{x^2}{(x+1)e^x}" and "\\frac{C}{(x+1)e^x}" are transient because as "x\\to \\infin" , both of these terms tend to 0.
Answer: "\\frac{x^2}{(x+1)e^x},\\frac{C}{(x+1)e^x}" .
Comments
Leave a comment